Subjective and objective evaluation of one’s physical fitness – the role of self-esteem, motivation, and the need for social approval - Piasecka, Agata; Kolmetz, Maria; Kotyśko, Martyna; Stankiewicz, Błażej (Journal of Education, Health and Sport, 2018)
Introduction and purpose of the work: Physical fitness is an important aspect of human life that can have an impact on biological, social, and psychological functioning. The aim of the research was to compare students who were engaged and those who were not engaged in sport in terms of self-evaluation of own physical fitness and performance in the Functional Movement ScreenTM. The analyses also included the role of motivation, self-esteem, and the need for social approval. Material and method: The participants of the study were students who do sports (n = 30) and those who are not engaged in a sport activity (n = 30) at one Polish university (aged 18-24 years, Mage = 21,23; SD = 1,5). The following instruments were used in the research: Self-Esteem Scale (SES), Social Approval Test (TAS-27), Sport Motivation Scale-II (SMS-II), Functional Movement ScreenTM (FMSTM), Survey about own physical fitness and sport related information.Results: The results revealed that active and inactive students differed in the subjective scores in the FMSTM and evaluation of own physical fitness. However, in both groups similar scores in self-esteem and the need for social approval were present. Subjective evaluation (made by the subjects) of own performance in the FMSTM was rated lower than objective one (made by the researchers) in both groups. The FMSTM scores (both objective and subjective) were related to different types of motivation. The lowest mean values were noted for external motivation and amotivation. Conclusions: The research has shown differences, in evaluation of physical fitness and FMSTM score - which can inform about the risk of potential injury - between the students who were engaged and those who were not engaged in sport. Motivation, need for social approval and self-esteem were mutually related. They can play an important role in shaping the belief about one’s physical fitness and the effect of one’s performance, although further investigations are needed as well as different types of statistical analyses to provide conformation for this assumption.